Combined intestinal and squamous metaplasia of the renal pelvis. Issue 2 (March 1969) - Salm, R.
Abstract : A case of combined squamous and intestinal metaplasia of the renal pelvis, associated with hydronephrosis, chronic pyelonephritis, and lithiasis, is reported. The changes are considered to be due primarily to mechanical irritation of the pelvic epithelium.